Aplikasi Online Berbasis Android “SI TekO” (Sistem Informasi Teknisi Online) Sebagai Solusi Mempermudah Masyarakat Dalam Mendapatkan Jasa Service - Akbar, Romi Nur asfi; Indiarto, Fahmi; Aristiantoro, Arfani; Utomo, Yudo; Indiarto, Fahm (Generation Journal, 2021)
In this industry 4.0 era, Indonesian people have been replaced by machines or computers, so researchers have created an SI-TekO-based application. As if when electronic goods, IT, or damaged installations want to repair or install tools at home, it will be easier to use online services. Services are often seen as a complicated phenomenon. The word service itself has many meanings, from personal service to service as a product. Production of services may be related to physical products or not. Very often the problem is when we are bothered at work so we lack the time to look for repair services for our electronic devices, and install the installation that we expect. Therefore the researchers created an android-based application called SI-TekO. The results of this study are Android-based applications that are SI-TekO.